Physico-chemical Studies and Thermodynamics of Some Transition Metal Complexes with 2-cis-3,7-Dimethyl 2,6-Octadiene-1-al - Sharma, Premlata; Nagar, Meena (Asian Journal of Chemistry, 2010)
Acyclic monoterpenoids form complexes with many transition metals. 2-cis-3,7-dimethyl 2,6-octadiene-1-al (citral) forms complexes with Fe(Ill), Co(II) and Ni(II). Stereochemistry of the complexes has been studied by physico-chemical methods.